Inclusão e aprendizagem do aluno com deficiência mental: expectativas dos professores - Sousa, Sônia Bertoni (Universidade Federal de São Carlos, 2008)
This research treats of the questions which more specifically result from the area of special education. However to discuss and permeate an amplified context of education, the world and society. This research has as its objective to analyze the expectations demonstrated by teachers from the common class room and of the specialized educational service of the public municipal network of Uberlândia/MG which has students with mental deficiencies (DM), in relation to learning the content proposed by the school and the inclusion of these students in the regular school framework. So as to attend the proposed objective an analytical-critical field survey was carried out. Questionnaires which contained open, closed and mixed questions were applied to the teachers, participants in the study. Seventy six (76) questionnaires from teachers from common class room were analyzed (PSC) and fifty five (55) questionnaires from teachers from specialized educational attention (PAEE). This corresponds to respectively 36.01% and 67.90% of the total population. For data analysis the percentage of answers presented by the respondents was analyzed as well as analyzing the content expressed in same. For a statistic analysis the chi-square-test (X²) was used for proportions which were expected to be unequal between the different populations object of the research (PAEE and PSC) and the chi-square-test (X²) for proportions which were expected to be equal among the same population. For the analysis of the data the answers were grouped together starting from the pre-definition of analysis categories and the qualitative interpretation of the collected data was made using the logic of separation and approach relating to the object under study while using the hermeneutical-dialectical analysis of reality. The principal results show that the expectations manifested by the teachers are that the students from the DM socialize and lean the school content; they also are in agreement that these pupils be included in a common class room provided that there be as much structural and economical changes as those of a behavioral nature and especially political. Also what prevailed in a hegemonic form for the two groups of teachers was that the social function of the school is to propitiate systematized knowledge, forming conscious, critical, autonomous citizens who are agents of necessary transformations so that there will be a better, fairer and equalitarian world. From the manner in which the conclusion was made one can affirm, that the functions which are attributed to the school in inclusive education and the expectations of the teachers are still incompatible with the practice of public education in vogue, as the schools continue to use structures of an organizational model type which intends to treat all as equal. But, in the face of an objective lack of structure and material resources, associated with a lack in amplification and incorporation, in fact, of a scientific and social-political reflection as to the nature of inclusion, there is an absence of effective conditions for this process to become concrete as a daily teaching policy practice in the school reality. Only from a resignification of the education concept in public schools and consequently of the construction of the necessary basis for the transformation of the present school organization, in that which refers to functioning structure, to knowledge, to time and to school area, will it be possible to advance and attend to the expectations of the teachers in regards to the student who has a mental deficiency and the adoption of a public policy which is effectively inclusive.
Keywords: Educação especial; Deficiência mental; Inclusão escolar; Aprendizagem; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL